Kinetically unstable 2–isocyanophenol isolated in cryogenic matrices: Vibrational excitation, conformational changes and spontaneous tunneling - Jesus, A. J. Lopes (2020)
Monomers of 2-isocyanophenol were generated in low-temperature solid Ar and N2 matrices by UV-irradiation of benzoxazole and characterized by infrared (IR) spectroscopy. Near–IR narrowband excitation of the first OH-stretching overtone of 2–isocyanophenol isolated in an N2 matrix converted the most stable cis into the higher-energy trans conformer. Interconversions between these conformers also occurred when the sample was vibrationally excited by the full, or filtered, broadband light of the IR spectrometer source, notably, with different isomerization rate constants. A spontaneous trans → cis decay, via H–tunneling, was observed for N2 matrix kept in dark. In an Ar matrix, only the cis conformer was observed.